To the moon! : the true story of the American heroes on the Apollo 8 spaceship - Kluger, Jeffrey (Philomel Books, 2018)
The true story of Apollo 8, the first manned American spaceship to break free of the Earth's orbit and reach the moon carrying Frank Borman, Jim Lovell, and Bill Anders-- the first astronauts ever to see the moon first hand. This books covers the frantic rush to get the rocket ready and the journey that gave a new look at Earth and our section of the solar system. Covers the science and training required to put people into space and what it is like to live in a spaceship.